Evaluation of prostate specific antigen level in different age group of Patients in Eastern part of Nepal - Shreewastav, Rupesh Kumar; Gaire, Chandra Prakash; Ghimire, Ashima; Shah, Prashant Kumar; Singh, Arambam Giridhari (Journal of Nobel Medical College, 2016)
Background A study was conducted to evaluate Prostate specific antigen (PSA) level in different age group of patients in Nobel Medical College Teaching Hospital (NMCTH), Biratnagar, Eastern Nepal. Material and Methods A total of 1870 male patients (age 51-88), attending OPD in different departments of NMCTH, were sent to Clinical Laboratory Services for estimation of Prostate specific antigen from 1st January 2013 to 30thJune 2014 and recruited for this study after Institutional ethical approval. Blood serum of these patients was tested for Prostate specific antigen level by Chemiluminescence Immunoassay (CLIA). Mean value and standard deviation were calculated using Student’s two–tailed t–test. Analysis of data was performed using one– way ANOVA. Results are considered statistically significant if p ≤0.05. Results Out of 1870 patients, 178 patients showed significantly higher level of PSA in their serum when compared to normal individuals. Out of this 178, 37 were from age group of 51-60, 51 were from age group of 61-70, 42 were from age group of 71-80 and 48 were from age group of 81-88. The remaining 1692 patients were having PSA within normal limit. PSA was found to be elevated up to a maximum of 34.5 ng/ml in patient. PSA level of <4 ng/ml was considered normal for this study. Conclusion This study, thus determines the diagnostic level of PSA, in different age group of patients comparing with normal individuals in eastern Part of Nepal that can help in diagnosis, prognosis and management of prostate cancer. Journal of Nobel Medical College Volume 5, Number 1, Issue 8, January-July 2016, 14-19